Pengaruh Profitabilitas, Ukuran Dewan Komisaris, Keterlibatan Perempuan dalam Dewan Direksi dan Koneksi Politik terhadap Kesulitan Keuangan - Ramerlin, Ramerlin; Nyale, M. Hendri Yan (LPPM Institut Pendidikan Nusantara Global, 2025)
Financial resilience extends beyond mere profit figures, encompassing the influence of leadership composition and external networks on corporate decision-making. This study investigates how profitability, board size, female representation in management, and political connections affect financial distress in infrastructure companies listed on the Indonesia Stock Exchange during 2021–2023. Using the Altman Z-Score as the primary measure of financial stability, data were collected from 51 companies, resulting in 153 observations through purposive sampling. The analysis uncovers a nuanced relationship between governance and financial health. Profitability emerges as a strong protective factor against financial distress, suggesting that firms generating higher profits are better positioned to withstand economic pressures. Conversely, larger boards of directors, the inclusion of women in managerial roles, and political connections appear to increase the likelihood of financial vulnerability, indicating that more complex governance structures and external affiliations may introduce risks or inefficiencies. Notably, the presence of women on commissioner boards shows no statistically significant impact, highlighting that effects may vary depending on the level of leadership. These findings emphasize that financial resilience is not solely determined by numerical performance but is intricately linked to leadership composition, diversity in decision-making, and political networks, underlining the multifaceted nature of corporate stability and the importance of strategic governance choices.